Genetic variation, heritability and genotype by environment interaction of morphological traits in a tetraploid rose population - Gitonga, Virginia W; Koning-Boucoiran, Carole FS; Verlinden, Kathryn; Dolstra, Oene; Visser, Richard GF; Maliepaard, Chris; Krens, Frans A (BMC genetics, 2014)
Global trade has ensured that the ornamental horticulture continues to grow worldwide, with rose hybrids being the most economically important genus (Rosa x hybrida). Due to changes in global trade and an increase in energy costs the ornamental industry has seen a shift in the production and sale of flowers from the US and Europe alone to production in Africa and Latin America. As Kenya is a major exporter of roses to Europe we studied the genetic variation and heritability of specific morphological traits in a tetraploid population grown in the Netherlands and in Kenya. The aim was to estimate genotype by environment interaction (G × E) and to investigate the implications of (G × E) for rose breeding. A tetraploid rose population (K5) from a cross between two tetraploid parents was field tested over two seasons in the Netherlands (summer and winter) and two locations in Kenya (Nairobi and Njoro). Ten traits were compared per genotype across the four environments. There were differences in trait association across the four environments showing that the traits were partially influenced by the environment. The traits that had a low ratio of σ(2) ge/σ(2) g also showed a high value for heritability. For the traits number of petals, prickles on petioles, prickles on stems the interaction is minimal. For the traits chlorophyll content, stem width and side shoots we observed a much higher interaction ratio of 0.83, 1.43 and 3.13 respectively. The trait number of petals had the highest heritability of 0.96 and the lowest σ(2) ge/σ(2) g ratio (0.08). The trait number of side shoots (SS) with the lowest heritability (0.40) also had the highest σ(2) ge/σ(2) g ratio of 3.13. Attained by this experiment showed that we have different magnitudes of non-crossover G × E interactions. For the traits number of petals, prickles on stems and prickles on petioles with a low interaction and high heritability, selection can be done at any of the environments. Thus, these traits can be confirmed at the breeding site. For the traits stem width, side shoots and chlorophyll content that had a higher interaction selection for or against these traits should be done at the production location or at least be verified there.